Pengaruh Dimensi Fraud Hexagon Terhadap Fraudulent Financial Statement pada Perusahaan Sektor Energi yang Terdaftar di BEI Tahun 2019-2022 - Muhammad Iqbal; Espa , Vitriyan (Jurnal Ilmiah Ekonomi Global Masa Kini, 2024)
The purpose of this research is to gain knowledge regarding the influence of the dimensions of hexagon fraud which consist of stimulus which is proxied by ROA, capability which is proxied by top management education level, collusion which is proxied by projects with the government, opportunities which are proxied by ineffective monitoring, rationalization which is proxied by the frequency of historical restatements, and ego proxied by the number of frequent CEO exposures to fraudulent financial statements. The sample in this research is energy sector companies listed on the IDX for the 2019-2022 period. The research is quantitative research using secondary data obtained from annual reports of energy sector companies listed on the IDX for the 2019-2022 period. The sample was selected using purposive sampling, the number of companies sampled was 18 companies with a research period of 4 years. Data analysis using WarpPLS 7.0. Based on this research, it is known that stimulus proxied by ROA has no effect on financial statement fraud, capability proxied by top management education level has a negative effect on financial statement fraud, collusion proxied by projects with the government has no effect on financial report fraud, proxied opportunities with ineffective supervision it has no effect on financial statement fraud, rationalization which is proxied by the frequency of historical restatements has no effect on financial report fraud, and ego which is proxied by the frequent number of CEO's pictures has no effect on financial report fraud in energy sector companies listed in IDX 2019-2022. Keywords: Fraud Hexagon, Fraudulent Financial Statement, Fraud, IDX, Energy Companies